(untitled) (ENTHYMEMA, 2011)
Eyal Segal argues for a functionalist approach to narrative studies. Commenting on his work on «narrative closure», he provides examples that show that the comprehension of texts’ endings is enriched by rhetorical analysis and inevitably misguided by mimetic approaches.